Forced Choices: Push-Pull Dynamics of Illegal Afghan Migration and Returnee Reintegration Experiences - A Mixed-Methods Analysis - AMIR, Ebad Ullah; YAR, Fayaz Gul Mazloum (Journal of Political And Legal Sovereignty, 2025)
Purpose:Complex factors—poverty, unemployment, insecurity, and lack of jobs—drive illegal migration from Afghanistan, which remains a major socio-economic challenge. While existing studies have explored the causes of migration, gaps remain in understanding the nuanced interplay between push and pull factors and the post-return experiences of Afghan migrants.Methodology:This study adopts a mixed-methods approach, incorporating quantitative surveys and qualitative interviews with 150 returnees from Iran, Pakistan, and selected European countries. Data were analyzed using SPSS and NVivo software.Findings:The findings reveal that economic deprivation, insecurity, and political instability are dominant push factors, whereas job opportunities, safety, and better quality of life in destination countries are key pull factors. Furthermore, returnees report significant challenges in reintegration, including socio-economic marginalization and lack of institutional support, increasing their risk of re-migration.Implication:This study contributes to migration scholarship by offering a contextualized analysis of Afghan returnees and highlighting the need for responsive policy frameworks to address the root causes of migration and support sustainable reintegration.